AN INVESTIGATION OF UNDERGRADUATE STUDENTS' ORAL COMMUNICATION STRATEGY (OCS) IN DEBATE CLASS - Indra Yoga Prawiro; Chintia Fita Diyales; Atikah Wati (English Language Education Department, Universitas Majalengka, 2022)
Dornyei (1995) classifies communication strategies based on the problem-oriented perspective. In this taxonomy, the oral communication strategies refer to the speakers’ strategies used when encountering some communication problems. This qualitative study was conducted in a descriptive case study to investigate undergraduate students’ oral communication strategy in debate class. The participants of this study were the third semester of undergraduate students who join in a critical speaking class. There were 24 students. The observation was used to obtain the data. The data has been collected from this instrument was analyzed using the steps from Gay et al. (2006) with memoing, describing, and classifying. The result of the study revealed that the students used 11 of 12 types of oral communication strategies. The first is message abandonment with 12 utterances (4.5%). The second is topic avoidance with five utterances (1.81%). The third is circumlocution with one utterance (0.37%). The fourth is an approximation with six utterances (2.25%). The fifth is using all-purpose words with five utterances (1.81%). The sixth is word coinage with five utterances (1.81%). The seventh is using non-linguistic means with 12 utterances (4.5%). The eighth is foreignizing with two utterances (0.75%). The ninth is code-switching, with 27 utterances (10.2%). The tenth is the appeal for help with 35 utterances (13.2%), and the last is the use of fillers applied by students with 157 utterances (58.8%). Meanwhile, the students do not apply the literal translation as a communication strategy when conducting a debate. It implies that the types of oral communication strategies used by the students in this study involve the ability to overwhelm language faults in English.